Inhalant Use Initiation among U.S. Adolescents: Evidence from the National Survey of Parents and Youth Using Discrete-Time Survival Analysis - Nonnemaker, James M. (2011)
The purpose of this paper is to identify factors associated with initiation to inhalant use among adolescents ages 9 to 18. The data are from the National Survey of Parents and Youth, a longitudinal household survey. Baseline surveys for adolescents and parents were conducted between November 1999 and June 2001 and then annually for three subsequent rounds. The outcome measure is an indicator of a respondent’s first use of inhalants. Discrete-time survival analysis was used to model the hazard of initiation. The hazard of inhalant initiation peaks at about 14 years of age (slightly younger than smoking and marijuana initiation). African Americans were less likely than Whites to initiate inhalant use, and higher family income was protective against inhalant initiation. The findings suggest that parenting is associated with initiation of inhalant use: parental drug use was a risk factor for inhalant initiation, and a measure of parental monitoring was protective. The study results also suggest a strong relationship between inhalant use and other problem behaviors and sensation seeking. These results highlight the need to intervene early for youth at risk of or just beginning to engage in risky behaviors including inhalant use.